COVID-19 Lockdown, Home Environment, Lifestyles, and Mental Health among Preschoolers in China - Yuting Zhang; Jin Zhao; Zhangsheng Yu; Guanghai Wang; Jun Zhang; Fan Jiang; Saishuang Wu; Yue Zhang; Donglan Zhang; Xi Chen (Institute of Labor Economics (IZA), 2024)
During the first wave of the COVID-19 pandemic, Shanghai implemented lockdown measures to stop transmission of the virus. Over 26 million residents, including 0.8 million children aged 3-6, were confined at home. This study leveraged a city-wide cohort of preschool children - the Shanghai Children's Health, Education and Lifestyle Evaluation, Preschool (SCHEDULE-P) - and used a quasi-experimental design to study the impact of lockdown on preschool children's mental health and changes in their home environment and lifestyles. Two cohorts - the pre-pandemic cohort and the pandemic cohort - were investigated and compared using the difference-in-differences approach. The Strengths and Difficulties Questionnaire was used to screen children who were at risk for mental health distress. The Index of Childcare Environment questionnaire was used to evaluate the quality and quantity of stimulation and support available to children in their family environment. Children's screen time, sleep duration, and household socioeconomic status were also queried. The results showed that having experienced lockdown and home confinement was associated with a 3.1% increase in the percentage of children at risk for mental health distress, was associated with 21.2 minutes/day longer screen time, 15.7 minutes/day longer sleep duration, and a less favorable family environment. Children of parents with lower levels of education were more likely to experience mental health challenges associated with the lockdown.
Keywords: I18; I12; H75; I28; C23; 330; lockdown; preschoolers; mental health; home environment; lifestyle; China; COVID-19